СИНТЕЗ ТА ДОСЛІДЖЕННЯ АНТИОКСИДАНТНОЇ АКТИВНОСТІ ДЕЯКИХ ПОХІДНИХ НА ОСНОВІ 4-ІМІНОТІАЗОЛІДИН-2-ОНУ - Чабан, Т. І. (Фармацевтичний часопис, 2015)
Synthesis and antioxidant activity evaluation of some novel derivatives based on 4-iminothiazolydine-2-one T.I. Сhaban Lviv, Danylo Halytsky Lviv National Medical University Summary: Thiazolydine derivatives belong to the group of biologically active compounds which are widely used in modern medical chemistry. They were shown to posses the wide range of biological actions. 4-Imino-2-thiazolydones are relatively unexplored with regard to their preparation synthetic protocols and biological action spectrum in the modern organic and pharmaceutical chemistry as compared to their 2-imino derivatives. Thus the objective of the present work was to synthesize a series of novel 4-imino-2-thiazolydone derivatives as the potential drug-like molecules. 3-Aryl-thiazolydine-2,4-dions were firstly prepared using the common synthetic protocol and they were then subjected to thionation reaction with phosphorus pentasulfide leading to the appropriate 3-aryl-4-thioxo-thiazolydin-2-ones obtaining. The above-mentioned derivatives were obtained under the conditions similar to that under which well-known 4-thioxo-thiazolydine-2-one (isorhodanine) synthesis was preceded. The synthetic potential of the synthesized compounds allowed 3-aryl-4-thioxo-thiazolydones treatment with 25 % ammonia aqueous solution leading to novel 3-aryl-4-imino-thiazolydine-2-one obtaining not mentioned in the scientific literature. The reaction proceeding was possible taking into account the advantage of thione group significant activity possessing in 3-aryl-4-thioxo-thiazolydine-2-ones as cyclic thioamides owing to stronger electrophilic properties of thiocarbonyl group carbon atom as compared with carbonyl group in C4 position of 3-aryl-thiazolydine-2,4-diones, consequently. One of the proofs of synthesized compounds structure was their acidic hydrolysis with 3-aryl-thiazolydine-2,4-ones generation. The presence of active methylene group in C5 position of 3-phenyl-4-imino-thiazolydine-2-one thiazolydine ring provided an entry for aldol condencation carrying out with the respective 3-phenyl-4-imino-thiazolydine-2-one 5-aryliden derivatives generation. We discovered that the high yield of the product could be achieved by introducing the equimolar amounts of 3-phenyl-4-imino-thiazolydine-2-one and appropriate aromatic aldehydes using monoaminoethanol as a catalyst. The next stage of our strategy included the core heterocycle further structural modification in its C5 position. In particular the nitrosylation reaction with nitrous acid was proceeded. It was found that 3-phenyl-4-imino-thiazolydine-2-one could interact with nitrous acid obtained in its turn under sodium nitrite treatment with hydrochloric acid. Nitrosylation reaction allowed to achiev novel 5-isonitrozo-4-imino-3-phenyl-thiazolydine-2-one which was not mentioned in chemical literature. The structures of the obtained compounds were confirmed by 1H NMR spectroscopy and elemental analysis. The antioxidant activity of the novel compounds was determined in vitro on basis of free radical scavenging activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical. DPPH radical has found many applications due to its high stability in a methanolic solution and intense purple color. In its oxidized form, the DPPH radical has an absorbance maximum centered at a wavelength about 540 nm. The absorbance decreases when the radical is reduced by antioxidants. Its reduction affords 2,2-diphenyl-1-picrylhydrazine (DPPH-H), or the corresponding anion (DPPH–) in basic medium. The DPPH radical acts as a scavenger for other odd-electron species which afford para-substitution products at phenyl rings. The pharmacology screening allowed to state that the synthesized compounds had been shown to possess the moderate antioxidant activity. So it may be concluded that the functionalization of 4-iminotiazolidyn-2-one by its N3 and C5 positions did not lead to the free-radical-scavenging activity enhancement.